Multidimensional Organisational Commitment of Public Servants in the Public Sector of Hanoi Capital - Nam, Nguyen Danh; Lan, Uong Thi Ngoc (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 2, 2022)
The study aims to analyse the impact of personality traits on multidimensional organisational commitment of public servants working at the Administrative units and in Public non-business units of the Hanoi People’s Committee in Vietnam. From the data provided by 587 public servants at the Administrative units and Public non-business units, the structural equation model was applied to evaluate the impact of personality traits on three components of organisational commitment. The results showed a positive relationship between conscientiousness, extroversion, and agreeableness with multidimensional organisational commitment. Besides, openness to new experiences and neuroticism are negatively correlated with multidimensional organisational commitment. The result of the study suggests significant implications for Administrative units and Public non-business units of the Hanoi People’s Committee to increase organisational commitment of public servants in the future.